Disability Awareness dalam Meningkatkan Pengetahuan Tentang Penyandang Disabilitas di Kelompok PKK RW 13 Pajang Surakarta - Ernawati, Sri; Riskiana Putri, Dhian; Rachmawati, annies; Purnomosidi, Faqih (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Indonesia is one of the countries with a large population of people with disabilities. Where society still does not realize and understand about disabilities and people with disabilities. This creates negative awareness among people with disabilities. This service activity aims to educate about disability awareness in the community, so that citizens become better able to understand disability. This community service activity is carried out using psychoeducational methods. The output of this service is (1) increased knowledge and understanding of the community (PKK group) about people with disabilities so that harmony is created, (2) partners have pocket books about people with disabilities so that disability awareness increases. The final result of this service is that participants, namely the PKK group, can understand and understand disabilities so that their knowledge increases, and participants are very enthusiastic in participating in this activity with question and answer discussions about children with disabilities. Participants in this service are PKK members in RW 13 Norowangsan Pajang.